Guest

Y=(1+tanA)(1-tanB) then A-B=π÷4 so (y+1)™(y+1)is Ka answer btayo

Y=(1+tanA)(1-tanB) then A-B=π÷4 so (y+1)™(y+1)is Ka answer btayo

Grade:12th pass

1 Answers

NIKUNJ DANKHARA
24 Points
3 years ago
Y=(1+tan((π/4)-B)(1+tanB)
Y=1+((1-tanB)÷(1+tanB))(1+tanB)
Y=[((1+tanB)+(1-tanB))÷(1+tanB)][1+tanB]
By equating this equation 
Y=2
So (2+1)™(2+1)
Ans=27
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free